PENGOLAHAN LEACHATE DENGAN MENGGUNAKAN MULTI SOIL LAYERING (MSL) - Monik Kasman; Peppy Herawati; Hikmah Hikmah (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Landfill leachate is defined as any contaminated liquid effluent percolating through deposited waste and emitted within a landfill or dump site through external sources, of which its route of exposure and toxicity often remains unknown. Leachate migration could be potential source of  run off and ground water pollutants. Hence, this research was objected to observe the effectivity of MSL method in reducing pollutant from leachate. This research was conducted by introducing landfill leachate of Talang Gulo down to MSL reactor 15x50x50 cm by gravity force. MSL reactor was installed by unpermeable layer and permeable layer. Unpermeabel layer was composed by mixed soil and activated carbon by ratio 2:1, while permeable layer was gravel with diameter 0,5 – 1,0 cm. The effect of hydraulic loading rate (HLR) which consisting of  250 l/m2.day, 500 l/m2.day and 1000 l/m2.day on reduced pollutan including pH, COD, ammoniac and pH value was observed. Based on the results, it was concluded that MSL method was able to reduce pollutant up to the percentage of 90%.  It was highly depends on HLR, the efficiency reduction increases as the HLR decreases. Efficiency for COD, ammoniac, and Fe were 53,457%, 98,325% and 88,5% respectively while pH value was  7,00 or neutral.Keywords:   reduction eficiency, Leachate, Multi Soil Layering (MSL)